Emergency use of nebulised bronchodilator drugs in British hospitals. Issue 7 (July 1987) - O'Driscoll, B R; Cochrane, G M
Abstract : A telephone survey was conducted to determine the emergency use of nebulised bronchodilator drugs by the registrar or senior house officer on duty for medical admissions at 67 British hospitals. All used a nebulised beta agonist (usually 5 mg salbutamol) as first line treatment for severe acute asthma or reversible obstructive lung disease. Twenty three doctors used ipratropium bromide occasionally and 38 used it frequently, usually mixing ipratropium and a beta agonist in the nebuliser chamber. Only five doctors routinely specified whether the nebuliser should be driven by air or by oxygen. In the case of a hypercapnic patient with chronic bronchitis, 11 respondents would not specify which gas should be used and a further 14 would use oxygen, a potentially dangerous practice. In the case of a hypoxic asthmatic patient, 22 doctors would not prescribe oxygen as the driving gas. The driving gas flow rate was almost invariably determined by nursing staff. Intravenous aminophylline was used by all 67 respondents (52 of them frequent users) but only 24 used intravenous beta agonists (five of them frequent users). It is concluded that nebulised bronchodilator drugs are the most commonly used treatment for acute asthma and reversible obstructive lung disease in hospital, but further instruction in their use is required for the staff who use them most frequently.